Induction of Th1 type-oriented humoral response through intranasal immunization of mice with SAG1-Toxoplasma gondii polymeric nanospheres. (5th November 2018) - Naeem, Huma; Sana, Madiha; Islam, Saher; Khan, Matiullah; Riaz, Farooq; Zafar, Zunaira; Akbar, Haroon; Shehzad, Wasim; Rashid, Imran
Abstract: About one-third of the world population is prone to have infection with T. gondii, which can cause toxoplasmosis in the developing fetus and in people whose immune system is compromised through disease or chemotherapy. Surface antigen-1 (SAG1) is the candidate of vaccine against toxoplasmosis. Recent advances in biotechnology and nano-pharmaceuticals have made possible to formulate nanospheres of recombinant protein, which are suitable for sub-unit vaccine delivery. In current study, the local strain was obtained from cat feces as toxoplasma oocysts. Amplified 957 bp of SAG1 was cloned into pGEM-T and further sub-cloned into pET28-SAG1. BL21 bacteria were induced at different concentrations of isopropyl β-d -1-thiogalactopyranoside for the expression of rSAG1 protein. An immunoblot was developed for the confirmation of recombinant protein expression at 35 kDa that was actually recognized by anti-HIS antibodies and sera were collected from infected mice. PLGA encapsulated nanospheres of recombinant SAG1 were characterized through scanning electron microscopy. Experimental mice were intraperitoneally immunized with rSAG1 protein and intra-nasally immunized with nanosphere. The immune response was evaluated by indirect ELISA. In results intra-nasally administered rSAG1 in nanospheres appeared to elicit elevated responses of specific IgA and IgG2a than in control. Nanospheres of rSAG1 are found to be a bio-compatible candidate for the development of vaccine against T. gondii.